Numerical Investigation of Multi-Floater Truss-Type Wave Energy Convertor Platform - Ruijia Jin; Jiawei Wang; Hanbao Chen; Baolei Geng; Zhen Liu (Energies, 2022)
In order to solve the hydrodynamic characteristics of the multi-floater truss-type wave energy convertor (WEC) platform, the mathematical model is established by using the high-order boundary element method based on potential flow theory, in which the floater and the platform are connected by the floating arm based on the lever principle. The mathematical model is applied to study the heave motion response of each floater of the multi-floater truss-type WEC platform, and the effects of the floater number and the floater arrangement on the motion responses of floaters, as well as the power generation of the WEC platform are analyzed. The effect of the hydraulic cylinder on the floater is simulated by linear damping, and then, the work of the hydraulic cylinder is used to generate electricity, so as to achieve the purpose of simulating the multi-floater WEC power generation device. Some useful conclusions are obtained through calculation, which can provide data support for the corresponding platform.